2008
DOI: 10.1001/archpedi.162.11.1009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parents' Wartime Deployment on the Behavior of Young Children in Military Families

Abstract: This study is the first to show that children aged 3 years or older with a deployed parent exhibit increased behavioral symptoms compared with peers without a deployed parent after controlling for caregiver's stress and depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(154 citation statements)
references
References 21 publications
6
146
1
1
Order By: Relevance
“…School staff in military-connected schools also reported that deployments may be associated with increased child anxiety (Chandra et al 2010b). Among young children, the association between parent deployment and child behavior was different in different age groups, per caregiver reports with more internalizing behavior being exhibited in children 3 years and older (Chartrand et al 2008). These reports of increased child distress during deployment were confirmed by the evaluations of medical claims data and school data.…”
Section: Current Eramentioning
confidence: 74%
“…School staff in military-connected schools also reported that deployments may be associated with increased child anxiety (Chandra et al 2010b). Among young children, the association between parent deployment and child behavior was different in different age groups, per caregiver reports with more internalizing behavior being exhibited in children 3 years and older (Chartrand et al 2008). These reports of increased child distress during deployment were confirmed by the evaluations of medical claims data and school data.…”
Section: Current Eramentioning
confidence: 74%
“…Our results add to the findings of recent previous studies that documented deployment-related changes in child behavior by linking them to clinically apparent psychological and behavioral issues that merit the clinical attention of a pediatric provider. 14,16 Previous research has documented the differences between paternally and maternally separated children. 19 One possible explanation is that the mothers remaining at home may be more likely to manifest their own mental health issues or that mothers are more likely to transfer their own mental health symptoms onto the child.…”
Section: Discussionmentioning
confidence: 99%
“…The age range of 3 to 8 years was chosen because it excluded the younger ages at which there are frequent well-child visits, corresponded to the ages included in previous studies that documented subclinical behavior changes, and included the developmental stage at which one of the authors (Dr Gorman) had observed an increase in behavioral concerns in his pediatric practice. 14,16 Children of National Guard or Reserve personnel were excluded. Each subject's demographic information and enrollment date were extracted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of young children may be especially susceptible to stress in the parent-child system (8). Because children's reactions to stressors are strongly related to those of at-home-caregivers (9)(10)(11), parents who model effective coping are more likely to create conditions for their children to cope well and to help them to develop their resilience. Parents that are functioning well are unlikely to be socially isolated or show symptoms of depression and are more likely to help their children to cope and to show them sensitivity.…”
Section: Introductionmentioning
confidence: 99%